Konferencje i szkolenia online zorganizowane w Polsce w czasie pandemii COVID-19 – wybór (od kwietnia 2022 do października 2022 roku) - Gamus, Paula (Acta Universitatis Lodziensis. Folia Librorum, 2022)
Selective list of conferences and trainings in the field of information and book science, as well as social communication and media, which were held online in Poland during the COVID-19 pandemic from April 2022 to October 2022.